Promoting financial stability of oil producers: Operational vs. financial hedging - Fang, Yiwei; Kang, Sang Baum; Lu, You (Journal of Financial Stability, 2023)
This paper investigates the effects of operational hedging on commodity price risks. It explores a novel type of operational hedging, i.e., the natural operational hedge position between upstream crude oil production and downstream activities in the supply chain. Using hand-collected data from 293 unique oil-producing firms, we find that operational hedging is sufficiently effective in reducing firms’ exposure to oil-price risk. We also find an inverse relationship between operational and financial hedging, suggesting that they can substitute for each other.